2017
DOI: 10.1093/nar/gkx023
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoid and cytoplasmic localization of small RNAs inEscherichia coli

Abstract: Bacterial small RNAs (sRNAs) regulate protein production by binding to mRNAs and altering their translation and degradation. sRNAs are smaller than most mRNAs but larger than many proteins. Therefore it is uncertain whether sRNAs can enter the nucleoid to target nascent mRNAs. Here, we investigate the intracellular localization of sRNAs transcribed from plasmids in Escherichia coli using RNA fluorescent in-situ hybridization. We found that sRNAs (GlmZ, OxyS, RyhB and SgrS) have equal preference for the nucleoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 94 publications
4
27
1
Order By: Relevance
“…showed that SgrS, an sRNA involved in the glucose-phosphate stress response, is roughly homogeneously distributed in the cytoplasm when its copy number is high, whereas when its expression is lower, it appears to be specifically absent from the central nucleoid region (105). A more comprehensive study of the localization of several several sRNAs, including GlmZ, OxyS, RyhB and SgrS, found equal preference for localization within cytoplasm and nucleoid region and no preferential membrane localization, or cell poles, as often observed for mRNAs by quantifying the signal overlap between RNA FISH and DAPI staining of DNA (106). Interestingly, the ability of a particular transcript to freely diffuse into the nucleoid region was correlated with the length and the translation activity of the RNA, because shortening and reducing translation of gfp mRNA led to the same localization as sRNAs and reduced nucleoid exclusion.…”
Section: Localization Of Small Rnasmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that SgrS, an sRNA involved in the glucose-phosphate stress response, is roughly homogeneously distributed in the cytoplasm when its copy number is high, whereas when its expression is lower, it appears to be specifically absent from the central nucleoid region (105). A more comprehensive study of the localization of several several sRNAs, including GlmZ, OxyS, RyhB and SgrS, found equal preference for localization within cytoplasm and nucleoid region and no preferential membrane localization, or cell poles, as often observed for mRNAs by quantifying the signal overlap between RNA FISH and DAPI staining of DNA (106). Interestingly, the ability of a particular transcript to freely diffuse into the nucleoid region was correlated with the length and the translation activity of the RNA, because shortening and reducing translation of gfp mRNA led to the same localization as sRNAs and reduced nucleoid exclusion.…”
Section: Localization Of Small Rnasmentioning
confidence: 99%
“…Therefore, in general, longer RNAs, including coding RNAs, have a lower propensity towards nucleoid localization compared to shorter, often non-coding transcripts. So far, the available studies on a handful of examples of sRNAs suggest an unbiased cellular localization (105, 106). It should be noted that investigation of sRNA localizations are predominately focused on non-coding regulatory RNAs.…”
Section: Localization Of Small Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a role for specific RNA binding proteins cannot be ruled out as drivers of the process, a simpler explanation is that the corresponding sequences endow the xyl transcripts with physical properties that make them to be quickly discharged from the vicinity of the nucleoid, especially if the transcribed sequences are large. In fact, it seems that smaller RNAs use to appear uniformly distributed throughout the bacterial cell, while longer molecules typically display more limited dispersion (47). Large mRNAs can hardly co-localize with densely packed DNA regions due to straight physical forces e.g.…”
Section: Disruption Of Intracellular Crowding Enables Xyl Transcriptsmentioning
confidence: 99%
“…However, should transcript diffusion away from the promoter and capture by ribosomes in a different cell location occur, confinement in given spots for translation could become apparent. Some mRNAs can indeed travel throughout the E. coli's interior (64) and translation inhibition makes RNA to remain closer to the nucleoid (47). This suggests that at least in some cases ribosomes in fact pull mRNA from the nucleoid towards the rest of the cytoplasm.…”
Section: Disruption Of Intracellular Crowding Enables Xyl Transcriptsmentioning
confidence: 99%